2009
DOI: 10.1097/aud.0b013e3181987063
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age, Hearing, and Working Memory on the Speech Comprehension Benefit Derived from an Automatic Speech Recognition System

Abstract: Participants were able to use partly incorrect and delayed subtitles to increase their comprehension of speech in noise, regardless of age and hearing loss. This supports the further development and evaluation of an assistive listening system that displays automatically recognized speech to aid speech comprehension by listeners with hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…While Besser et al (2012) and Zekveld, Kramer, et al (2011) found associations between age and different TRT versions in groups of NH individuals with age ranges of 18 to 78 and 46 to 73 years, respectively, Koelewijn et al (2012) and Zekveld et al (2007) did not find such associations in NH groups with comparable age ranges. Also, in a secondary analysis of combined data from the studies by Zekveld et al (2007Zekveld et al ( , 2008Zekveld et al ( , 2009, no association between TRT performance and age was found (r = .16, p > .1) in a large group of NH individuals at ages between 18 and 78 years ).…”
Section: Linguistic Processing Abilitymentioning
confidence: 55%
“…While Besser et al (2012) and Zekveld, Kramer, et al (2011) found associations between age and different TRT versions in groups of NH individuals with age ranges of 18 to 78 and 46 to 73 years, respectively, Koelewijn et al (2012) and Zekveld et al (2007) did not find such associations in NH groups with comparable age ranges. Also, in a secondary analysis of combined data from the studies by Zekveld et al (2007Zekveld et al ( , 2008Zekveld et al ( , 2009, no association between TRT performance and age was found (r = .16, p > .1) in a large group of NH individuals at ages between 18 and 78 years ).…”
Section: Linguistic Processing Abilitymentioning
confidence: 55%
“…This benefith as been verified to apply also to hearing impaired persons by comparing young normal hearing persons, middle aged normal hearing persons and hearing impaired persons [39]. From that is wass een that age and hearing impairment reduce the benefite ff ects, buto verall ab enefiti nt he order of 2dBi so bserved for ASR performance of 74% which reduces to 0.5 to 1dBb enefit at ASR accuracyo f3 7%.…”
Section: Automatic Speech Recognition To Assist Speech Understandingmentioning
confidence: 95%
“…Consequently, this implied that subjective rating is not a good measure of listening effort when speech intelligibility is high. In hindsight, it was not surprising that there was no correlation between subjectively rated listening effort and the objective measure of effort, since this also had been reported in other studies (Anderson Gosselin & Gagné, 2011;Fraser et al, 2010;Hicks & Tharpe, 2002;Larsby et al, 2005;Zekveld et al, 2010;Zekveld et al, 2009). As a result, subjectively rated listening effort was not used in study 3 or in study 4.…”
Section: Subjective Measure Of Listening Effortmentioning
confidence: 96%
“…Instead audiologists and hearing aid dispensers need inquire and ask the hearing aid user about their experienced listening effort. Many studies have involved a subjective measure of listening effort (Anderson Gosselin & Gagné, 2011;Fraser, Gagné, Alepins, & Dubois, 2010;Hicks & Tharpe, 2002;Larsby et al, 2005; N. Rönnberg et al, 2014b;Zekveld, Kramer, & Festen, 2010;Zekveld, Kramer, Kessens, Vlaming, & Houtgast, 2009). However, consistent for these studies is the lack of correlation between the objective and the subjective measure listening effort, regardless of experimental conditions or participants.…”
Section: Listening Effortmentioning
confidence: 99%